2017
DOI: 10.1080/13880209.2017.1283338
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle formulation increases Syzygium cumini antioxidant activity in Candida albicans -infected diabetic rats

Abstract: Context:Syzygium cumini (L.) Skeels (Myrtaceae) is a medicinal plant widely used in folk medicine for the treatment of diabetes mellitus (DM). However, studies on the use of this plant and of nanoparticle formulations against DM-related fungal infections are scarce.Objective: To evaluate the effect of the treatments with aqueous seed extract of S. cumini (ASc) and ASc-loaded polymeric nanoparticles (NPASc) on biochemical parameters in Candida albicans-infected diabetic rats.Materials and methods: Male Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Tables 2 and 3 were used to organize the information gained from each study [11][12][13][14][15][16][17][18][19]. Table 2 displays data from combined in vivo/in vitro studies whilst Table 3 contains information from in vitro studies only .…”
Section: Data Extractionmentioning
confidence: 99%
“…Tables 2 and 3 were used to organize the information gained from each study [11][12][13][14][15][16][17][18][19]. Table 2 displays data from combined in vivo/in vitro studies whilst Table 3 contains information from in vitro studies only .…”
Section: Data Extractionmentioning
confidence: 99%
“…The crude polyphenol extract of java plums was nanoencapsulated and their antioxidant and hypoglycemic effects determined [64,119]. Compared to the free-form of the drug, it was found that the polymeric nanoparticles were able to effect changes in lowering blood glucose, cholesterol, creatinine, serum and pancreatic advanced oxidation protein products (AOPP).…”
Section: Crude Polyphenol Extractmentioning
confidence: 99%
“…MTF as such or as lyophilized alginate beads loaded with the plain drug or as chitosomal or niosomal dispersion, all at a dose of 200 mg kg À1 body weight, were dispersed in water and orally administered to rats by gavage (Owolabi and Omogbai, 2013;Bitencourt et al, 2017). Lyophilized empty chitosomal or niosomal beads were also administered to evaluate the possible effects of the formulation components.…”
Section: In Vivo Studiesmentioning
confidence: 99%